Design, Television, and Cultural Memory. The Open University’s A305 Course as a Case of Media Archaeology in Education - Manfra, Marco; Quercia, Grazia (Unlocking Television Archives in the Digital Era. 16th Media Mutations International Conference, 2026)
This paper examines the critical role of television archives in recovering forgotten histories of pedagogical experimentation, focusing on the Open University’s A305 course, History of Architecture and Design 1890–1939. It contextualizes the shifting perception of television – from an ephemeral medium to a rediscovered educational tool – and highlights how early disregard for its academic potential contributed to the disappearance of valuable content. A305, developed in collaboration with the BBC, represented a pioneering model of distance education. Combining television, radio, print, and interactive assignments, it broke academic barriers by bringing architectural and design history into domestic spaces, reaching both enrolled students and a broader public audience. Its multimedia structure enabled a participatory, dynamic learning experience. Architect Joaquim Moreno’s reconstruction of the course – through archival recovery, digitization, and exhibition – reveals the scope and innovation of this pedagogical experiment, reframing the archive as an active medium of cultural transmission rather than a passive memory bank. Through the lens of A305, the paper argues that television, when treated as an ecological and convergent medium, can serve as a powerful vector of knowledge production while inviting to a reconsideration of media archives as sites for educational reinvention and cultural reactivation in the present.